Determinant Factor Career Readiness in Final Year Undergraduate Students - Rahmi Dwi Febriani; Neviyarni Neviyarni; Marjohan Marjohan; Ifdil Ifdil; Afdal Afdal (Jurnal Neo Konseling, 2022)
Career readiness is very important for a students future career success. Career readiness is how much individuals are willing to exert themselves to achieve career goals. Based on the phenomena in the field, there are still  many college graduates who work not according to their study background, after completing their undergraduate education, they are not ready to face the competition in the world of work. This paper gives a theoretical  overview of the  careereadiness of college students. This research is a literature study, a method used to collect data or sources related to the topic raised in a study. The data about the determinant factors that affect career readiness that have been obtained are then analyzed using descriptive analysis methods.